A Corn Oil–Based Diet Protects Against Combined Ethanol and Iron‐Induced Liver Injury in a Mouse Model of Hemochromatosis. (6th June 2013) - Tan, Terrence C. H.; Crawford, Darrell H. G.; Jaskowski, Lesley A.; Murphy, Therese L.; Santrampurwala, Nishreen; Crane, Denis; Clouston, Andrew D.; Subramaniam, V. Nathan; Anderson, Gregory J.; Fletcher, Linda M.
<x xml:space="preserve">Abstract</x> Background Combined iron overload and alcohol may promote synergistic chronic liver injury and toxicity. The role of specific dietary fats in influencing the development of co‐toxic alcoholic liver disease needs further evaluation and is investigated in this study. Methods Wild‐type (WT) and the iron‐loaded Hfe‐null (Hfe−/−) mice were fed chow (CC), a AIN‐93G standard control (SC), or a corn oil–modified, AIN‐93G‐based (CO) diet with or without the addition of 20% ethanol (EtOH) in the drinking water for 8 weeks and assessed for liver injury. Results WT mice on CC, SC, and CO diets had no liver injury, although mild steatosis developed in the SC and CO groups. The addition of EtOH resulted in mild steatohepatitis in WT mice fed SC but not those on a CO diet. EtOH administration in Hfe−/− animals on the CC and SC diets caused marked oxidative stress, inflammatory activity, and subsinusoidal and portal–portal tract linkage fibrosis with significant up‐regulation of genes involved in cellular stress signaling and fibrogenic pathways. These effects were abrogated in the CO‐fed mice, despite elevated serum EtOH levels and hepatic iron concentrations, reduced hepatic glutathione and mitochondrial superoxide dismutase activities. Feeding with the CO diet led to increased hepatic glutathione peroxidase and catalase activities and attenuated alcohol‐induced hepatic steatosis in the Hfe−/− animals. Iron and EtOH feeding markedly reduced p‐STAT3 and p‐AMPK protein levels, but this effect was significantly attenuated when a CO diet was consumed. Conclusions A CO‐based diet is protective against combined EtOH‐ and iron‐induced liver toxicity, likely via attenuation of hepatic steatosis and oxidative stress and may have a role in the prevention of fibrosis development in chronic liver disease.